Forms of Procedural Abuse - Torki, Ali Abdelhamid; Almarzouqi , Noura Ibrahim ahmed (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: The study aimed to elucidate the extent of legal protection provided by criminal laws in Jordan and the United Arab Emirates (UAE) in deterring both general and specific crimes of child sexual exploitation through electronic games, considering them as crucial means exploited by criminals to commit this heinous and despicable crime against the most vulnerable segments of society. Methods: The study followed a descriptive, analytical, and comparative methodology. The descriptive approach involved studying the relevant Jordanian and Emirati laws concerning child sexual exploitation through electronic games. The analytical approach entailed analyzing these laws, while the comparative approach involved comparing Jordanian and Emirati laws to highlight strengths and weaknesses in each law. Results: The study found that the Jordanian legislator did not explicitly stipulate the necessary measures to protect children from the sexual exploitation they may encounter. In contrast, the Emirati legislator explicitly included such measures as they directly contribute to both treatment and prevention to prevent child sexual exploitation. Conclusions: The study recommends that the Jordanian legislator explicitly include provisions in the Jordanian Electronic Crimes Law, as the Emirati legislator did in the Emirati Electronic Crimes Law, regarding the crime of electronic sexual harassment. Additionally, the study suggests that the Jordanian legislator should add necessary measures to protect children from sexual exploitation in the Jordanian Child Rights Law, similar to those included by the Emirati legislator in Article (54) of the Child Rights Law.